2017
DOI: 10.1090/qam/1493
|View full text |Cite
|
Sign up to set email alerts
|

$L^\infty $ estimates for the JKO scheme in parabolic-elliptic Keller-Segel systems

Abstract: Abstract. We prove L ∞ estimates on the densities that are obtained via the JKO scheme for a general form of a parabolic-elliptic Keller-Segel type system, with arbitrary diffusion, arbitrary mass, and in arbitrary dimension. Of course, such an estimate blows up in finite time, a time proportional to the inverse of the initial L ∞ norm. This estimate can be used to prove short-time well-posedness for a number of equations of this form regardless of the mass of the initial data. The time of existence of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…There, it was also shown that the free energy functional E is ξ-convex for m ≥ 1 − 1 d in the set of bounded densities L ∞ (R d ) ∩ P 2 (R d ) with a given fixed bound allowing the use of the recent theory of ξ-convex gradient flows in [39]. Summarizing, the recent results for the Newtonian attractive kernel [39,30,33] allow for a rigorous gradient flow structure of the Newtonian attractive kernel case for m ≥ 1 − 1 d with initial data in L ∞ (R d ) ∩ P 2 (R d ).…”
Section: 4mentioning
confidence: 93%
See 1 more Smart Citation
“…There, it was also shown that the free energy functional E is ξ-convex for m ≥ 1 − 1 d in the set of bounded densities L ∞ (R d ) ∩ P 2 (R d ) with a given fixed bound allowing the use of the recent theory of ξ-convex gradient flows in [39]. Summarizing, the recent results for the Newtonian attractive kernel [39,30,33] allow for a rigorous gradient flow structure of the Newtonian attractive kernel case for m ≥ 1 − 1 d with initial data in L ∞ (R d ) ∩ P 2 (R d ).…”
Section: 4mentioning
confidence: 93%
“…[39] has shown that the gradient flow is well-posed if the energy E is ξ-convex, where ξ is a modulus of convexity. [33] has recently shown that for (1.1) with attractive Newtonian potential, for any ρ 0 in L ∞ (R d ) ∩ P 2 (R d ), there is a local-in-time gradient flow solution. The authors show that there are local in time L ∞ bounds at the discrete variational level allowing for local in time well defined gradient flow solutions.…”
Section: 4mentioning
confidence: 99%
“…From the perspective of approximating gradient flows, which are solutions of diffusive partial differential equations (3), such regularity and positivity can be guaranteed as long as the initial data are smooth and positive and either the diffusion is sufficiently strong or the drift and interaction terms do not cause loss of regularity. On the other hand, developing conditions on the energy and initial data that ensure such regularity and positivity holds at the level of the JKO scheme, for minimizers of Problem 1, remains largely open: results on the propagation of L p (R d ) or BV bounds along the scheme have only recently emerged [17,50,63].…”
Section: Remarkmentioning
confidence: 99%
“…For general Φ, we use some ideas from the proof of [16,Theorem 1]. Let us approximate S with a sequence (S ε ) ε>0 of smooth convex functions such that S ε c ε > 0 for any ε > 0 with S ε (0+) = −∞.…”
Section: ] For Instance)mentioning
confidence: 99%